2010
DOI: 10.1152/ajplung.00220.2009
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying epithelium-dependent relaxation in rat bronchioles: analogy to EDHF-type relaxation in rat pulmonary arteries

Abstract: Kroigaard C, Dalsgaard T, Simonsen U. Mechanisms underlying epithelium-dependent relaxation in rat bronchioles: analogy to EDHFtype relaxation in rat pulmonary arteries. Am J Physiol Lung Cell Mol Physiol 298: L531-L542, 2010. First published January 29, 2010 doi:10.1152/ajplung.00220.2009.-This study investigated the mechanisms underlying epithelium-derived hyperpolarizing factor (EpDHF)-type relaxation in rat bronchioles. Immunohistochemistry was performed, and rat bronchioles and pulmonary arteries were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 54 publications
1
19
0
Order By: Relevance
“…The existence of functional SK2 in human and mouse cardiac myocytes has been reported, and genetic knockout of SK2 results in a delay in cardiac repolarization and atrial arrhythmias [32]. Functional SK3 channels are associated with a variety of smooth muscle tissues, such as the smooth muscle of blood vessels [33], bronchus [34], bladder [35], and uterus [12]. Moreover, SK3 channels participate in the purine-induced inhibition of colonic smooth muscle contraction [36].…”
Section: Discussionmentioning
confidence: 99%
“…The existence of functional SK2 in human and mouse cardiac myocytes has been reported, and genetic knockout of SK2 results in a delay in cardiac repolarization and atrial arrhythmias [32]. Functional SK3 channels are associated with a variety of smooth muscle tissues, such as the smooth muscle of blood vessels [33], bronchus [34], bladder [35], and uterus [12]. Moreover, SK3 channels participate in the purine-induced inhibition of colonic smooth muscle contraction [36].…”
Section: Discussionmentioning
confidence: 99%
“…In pulmonary arteries relaxation sensitive to blockers of the K Ca 2.3 and K Ca 3.1 channels has been observed in several studies [26], [28][30]. Moreover, the potent K Ca 2.3- and K Ca 3.1 channel activator NS309 (6,7-dichloro-1H-indole-2,3-dione 3-oxime) has been shown to induce relaxation being sensitive to K Ca 2.3- and K Ca 3.1 blockade in rat and human pulmonary arteries [26], [27], rat mesenteric arteries [31], and in porcine retinal arterioles [32]. In addition, K Ca 3.1 expression has also been found in proliferating vascular smooth muscle cells [33], [34], and it may also be increased in the smooth muscle of the hypertrophied arteries in pulmonary hypertension.…”
Section: Introductionmentioning
confidence: 87%
“…In previous studies we have performed immunoblotting of lungs from rat and man [26], [27], but unfortunately we were unable to validate the gene expression results in this study with protein quantification in mouse lung using western blotting, as we experienced a series of difficulties (e.g. lack of specificity and multiple bands) with the mouse antibodies for the K Ca 2.3 and K Ca 3.1 channels, despite trying several types (K Ca 2.3: SC-28621 (Santa Cruz Biotechnology, Santa Cruz, CA); APC-025 (Alamone Labs, Jerusalem, Israel); H00003782-A01 (Abnova, Taiwan).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that the relaxation was only reduced but not abolished might be explained either by an incomplete epithelium denudation or by the existence of a concomitant epithelium-independent relaxing mechanism. Recently, it has been shown that K + channels participate to epithelium-dependent relaxation in guinea-pig trachea and rat bronchioles (Benoît et al, 2001;Kroigaard et al, 2010). This mechanism might be the underlying explanation of the epithelium-and K + channels-dependency of the Dichrostachys cinerea EtOH/H 2 O extract relaxing effect.…”
Section: Discussionmentioning
confidence: 95%